Archaeological internships as a factor in the formation of professional competences of a specialist in the specialty 032 "History and archeology - Bakumenko, O. (Problems of Engineer-Pedagogical Education, 2023)
The modern education system is oriented towards a mandatory combination of theoretical and practical teaching methods. Each of the currently existing educational and vocational training programs (EVTP) offers students a list of internships that should deepen and consolidate the theoretical knowledge obtained during classroom classes, and therefore contribute to the full formation of the graduate's basic professional competences. Today, the programs of educational and industrial internships are constantly being improved, taking into account the competence-based approach to education. The author of the article makes an attempt to analyze how and with which toolkit one of the types of compulsory training (archaeological) internships affects the formation of professional competences and the achievement of program learning outcomes of students studying at the EVTP "Local Studies and Tourism", specialty 032 " History and Archeology". Analyzing the program of the internship and programs of related disciplines, the author shows exactly which competences can be formed thanks to archaeological internships. The main stages and content of the archaeological internship, which is conducted by the teachers of the corresponding EVTP for first-year students, are considered. The article defines the main types of work and activities that make up the content of the archaeological internship and their influence on the development of professional competences. Particular attention is paid to the influence of the archaeological internship on the activation of students' educational and scientific activities and its educational significance. The internship involves nurturing a careful attitude to historical and cultural monuments and their rational use, familiarization with measures to protect the surrounding environment and historical heritage, etc. Students learn to treat historical and cultural heritage with respect, realize the role that proper field research plays in its preservation. In the article, attention is also focused on the skills necessary for the further professional and everyday life of specialists that this type of internships develops. It can be said with certainty that archaeological internship contributes to the formation of a number of important personal qualities necessary for any specialist, and allows students to demonstrate their creative and organizational abilities.